Analisis Pengaruh Penambahan Material Komposit Serat Kulit Durian Terhadap kekuatan Impak Batubata - Christina Bastian; Yoel Pasae; Yafet Bontong; Yous Yamhin (Universitas Muhammadiyah Metro, 2026)
Brick is a durable, water-resistant construction material that reduces rainwater seepage through walls and offers fire resistance, making it safer to use. This study aims to analyze the effect of adding durian husk fiber to bricks. Durian husk fiber was selected due to its high cellulose content and potential as an eco-friendly natural reinforcing agent. Fiber treatment involved cold smoking (at 35°C–45°C) for varying durations—no smoking, 5 hours, 10 hours, 15 hours, and 20 hours—to enhance surface quality and bonding with the matrix. An experimental method was employed, utilizing varying volume fractions of clay, durian husk fiber, and cassava starch: 50%:10%:40%, 50%:20%:30%, and 50%:30%:20%. Specimens were fabricated using the hand lay-up method and oven-dried for one hour at 200°C. Impact strength was assessed using the Charpy Impact Test method in accordance with ASTM D5942-96 standards. The results indicate that the highest absorbed energy value (13.096 Joules) was achieved with the 50%:30%:20% volume fraction and a 5-hour smoking treatment, while the lowest value (6.976 Joules) was observed with the 50%:20%:30% volume fraction and a 10-hour smoking treatment. Similarly, the highest impact strength value (0.163 J/mm²) was recorded for the 50%:30%:20% volume fraction with 5 hours of smoking, and the lowest (0.087 J/mm²) for the 50%:20%:30% volume fraction with 10 hours of smoking. These findings demonstrate that material composition significantly influences brick toughness, where an optimal fiber addition enhances energy absorption and inhibits crack propagation. It can be concluded that a volume fraction composition of 50%:30%:20% represents the optimum condition for enhancing the impact strength of composite bricks based on durian husk fibers and a cassava starch matrix. An excessive increase in fiber fraction tends to reduce impact strength due to diminished matrix bonding and increased material porosity.